An analysis of technology issues in mobile augmented reality - Pinandita, Tito; Mohamad, Siti Nurul Mahfuzah; Azman, Farah Nadia; Himawan, Hidayatulah (Slovene Society Informatika, 2023)
Augmented reality technology is currently increasingly modern and growing rapidly, this research is a summary of the popularity of augmented reality technology to the present. augmented reality application is increasingly being used in the fields of education, health and even used for the military. Other research describes combining augmented reality with other technologies. This study is to discover challenges and opportunities for future augmented reality applications. some studies illustrate that there are still some flaws in augmented reality technology. Hopefully in the future the deficiencies found in previous studies can be corrected.